Automated question answering via natural language sentence similarity: Achievements for Brazilian e-commerce platforms - Chico, Víctor Jesús Sotelo; Zucchi, Luiz; Ferragut, Daniel; Caus, Rodrigo; de Freitas, Victor Hochgreb; dos Reis, Julio Cesar (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2023: Anais do XIV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2023)
Chatbots have become indispensable for quickly answering e-commerce customer queries, which is crucial for selling products online. However, in Brazilian e-commerce, finding scalable chatbot solutions can be challenging. This article proposes an automatic question-answering system by replying to incoming questions with Frequently Asked Questions from stores. Our solution builds a store-specific database populated with question-answer pairs by generating the embedding of questions. We define a retrieval process by ranking candidate questions with a neural network to reuse the questions' known answers. Our solution was deployed and evaluated with data in the Portuguese and Spanish languages for several stores in South America's biggest e-commerce platforms. The development approach achieved 97.75% of satisfaction with the given answers.